Defining Engagement in Adolescent Substance Abuse Treatment. Issue 3 (18th September 2013) - Pullmann, Michael D.; Ague, Starcia; Johnson, Tamara; Lane, Stephanie; Beaver, Kevon; Jetton, Elizabeth; Rund, Evangejalynn
Abstract: Youth engagement in substance use treatment is an important construct for research and practice, but it has been thinly and inconsistently defined in the literature. Most research has measured engagement by initiation, attendance, and retention in treatment. Because youth generally enter substance use treatment as a result of compliance with external requirements, defining engagement in this way might be insufficient. This qualitative participatory research study describes five focus groups with 31 adults working with youth in substance use treatment. Focus groups were designed and conducted by youth researchers in collaboration with university‐based partners. We categorized participants' descriptions of engagement into five domains, identified as "CARES": Conduct, Attitudes, Relationships, Empowerment, and Social Context. These domains represent a comprehensive and ecologically‐based definition of engagement that situates engagement in the context and trajectory of youth development, has clear implications for assertive clinical practice, and provides a foundation for developing an operationalized measure.